A Comparative Study between Pathogenicity of Ceftazidime Resistant and Sensitive Escherichia coli in White Mice Kidneys and Bladder - Hammadi, Ali H.; Q. Alani, Mohammed; F. Al-Mathkhury, Harith J. (Iraqi Journal of Science, 2023)
Twelve albino mice was divided randomly into four groups comprising A through D injected with ceftazidime at sub MIC, Escherichia.. coli 11, Escherichia.. coli 11 with ceftazidime solution, and standard strain, respectively. Histopathological sections did not show any changes in respect to group A. however, group C suffered signs of infection less than those appeared in group B sections. Simultaneously, group D suffered intense histpathological changes more than other groups infected with resistant isolate.